Physics of 2D Materials for Developing Smart Devices - Goel, Neeraj; Kumar, Rahul (Nano-Micro Letters, 2025)
Rapid industrialization advancements have grabbed worldwide attention to integrate a very large number of electronic components into a smaller space for performing multifunctional operations. To fulfill the growing computing demand state-of-the-art materials are required for substituting traditional silicon and metal oxide semiconductors frameworks. Two-dimensional (2D) materials have shown their tremendous potential surpassing the limitations of conventional materials for developing smart devices. Despite their ground-breaking progress over the last two decades, systematic studies providing in-depth insights into the exciting physics of 2D materials are still lacking. Therefore, in this review, we discuss the importance of 2D materials in bridging the gap between conventional and advanced technologies due to their distinct statistical and quantum physics. Moreover, the inherent properties of these materials could easily be tailored to meet the specific requirements of smart devices. Hence, we discuss the physics of various 2D materials enabling them to fabricate smart devices. We also shed light on promising opportunities in developing smart devices and identified the formidable challenges that need to be addressed. Highlights: 1 Extensively discussed the physics of various two-dimensional materials enabling them to fabricate smart devices. 2 Statistical and quantum physics for understanding the functioning of smart electronic devices with strategies for improving their performance. 3 New advancement in device architectures for developing smart devices.